The Effect of the Number of Fins on Rocket Aerodynamic Performance Using Computational Fluid Dynamics - Mohamad Yamin; Nuril Hadi (Bincang Sains dan Teknologi, 2026)
This study aims to analyze the effect of the number of fins on the aerodynamic characteristics of a rocket using the Computational Fluid Dynamics (CFD) method. Three rocket configurations with different numbers of fins (3, 4, and 6 straight fins) were modeled and simulated at a subsonic speed of Mach 0.6 with angles of attack ranging from 0° to 25°. The main aerodynamic parameters analyzed include the lift coefficient (Cl), drag coefficient (Cd), and moment coefficient (Cm). The simulation results show that increasing the number of fins tends to improve rocket stability and produces a more uniform pressure distribution. The six-fin configuration yields the highest Cl/Cd ratio, particularly at an angle of attack of 10°, indicating the best aerodynamic efficiency. In addition to aerodynamic performance, economic considerations are also an important factor; the use of six fins provides advantages in terms of stability, although it requires higher manufacturing costs compared to three or four fins. Overall, the six-fin configuration is recommended for rocket applications that req uire high stability and aerodynamic efficiency.